The relationship between job satisfaction and job performance among employees in Tradewinds Group of Companies - Anuar Hussin (2011)
This study tries to determine the level of job satisfaction & job performance and to identify the relationship between job satisfaction components (which are pay, promotion, the work itself, supervision, & co-workers) and job performance among employees of Tradewinds Group of Companies. The study was conducted among 115 respondents in Tradewinds Group of Companies in Klang Valley. In this study, the whole population method was used. The study revealed that there was a positive relationship between job satisfaction components which were promotion, work itself, supervision and co-workers except for pay towards employee job performance. There was a significant difference between position and job performance. It proved that job satisfaction dimensions (pay, promotion, work itself, supervision and co-workers) can contribute to 17.8 percent (%) to increase the job performance in the organization. (Abstract by author)